Positivity preserving results for a biharmonic equation under Dirichlet boundary conditions - Omrane, Hanen Ben; Khenissy, Saïma (My University, 2014)
We prove a dichotomy result giving the positivity preserving property for a biharmonic equation with Dirichlet boundary conditions arising in MEMS models. We adapt some ideas in [H.-Ch. Grunau, G. Sweers, Positivity for equations involving polyharmonic operators with Dirichlet boundary conditions, Math. Ann. 307 (1997), 589–626].
Opuscula Mathematica
Keywords: biharmonic equation; positivity preserving; Dirichlet problem